How Physician Compensation and Education Debt Affects Financial Stress and Burnout: A Survey Study of Women in Physical Medicine and Rehabilitation. Issue 8 (1st February 2021) - Verduzco‐Gutierrez, Monica; Larson, Allison R.; Capizzi, Allison N.; Bean, Allison C.; Zafonte, Ross D.; Odonkor, Charles A.; Bosques, Glendaliz; Silver, Julie K.
Abstract: Objective: To investigate the contribution of financial stress to physician burnout and satisfaction among women physiatrists. Relationships among education debt and compensation with demographic, sociologic, and workplace factors were also assessed. Design: This was a cross‐sectional survey study of women physicians in the field of physical medicine and rehabilitation (PM&R) in the United States. The survey consisted of 51 questions covering demographic information (current and maximum education debt, race/ethnicity, years out of training, practice type and setting, hours worked, family structure, and domestic duties), work/life satisfaction, and burnout. The association between current/maximum debt and demographic characteristics, work/life satisfaction, and physician burnout were examined. Results: Of the 245 U.S. women attending physiatrists who met inclusion criteria, 222 (90.6%) reported ever having education debt (median category $101 000‐150 000) and 162 (66.1%) reported current debt (median category ≤ $50 000). Of these participants, 218 (90.5%) agreed that they would have fewer burnout symptoms if they were able to do more work that is core to their professional mission and 226 (92.2%) agreed that feeling undervalued at work is linked to physiatrists' burnout symptoms. Greater debt was seen in those who identified as Black/African American, were fewer years out of training, practiced general physiatry, and had both inpatient and outpatient responsibilities. Greater current debt had a significant relationship with measurements of work/life dissatisfaction. Burnout was associated with higher debt, lower compensation, more hours worked per week, and fewer hours of exercise performed per week. Conclusions: This study examined women physiatrists' perceptions of financial stress and found that greater education debt was associated with personal life dissatisfaction, career regret, and burnout. Further research is needed to address related causes and solutions.